PENGARUH KOMITMEN ORGANISASI, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA KEUANGAN PEMERINTAH (Studi Empiris SKPD Kabupaten Kepulauan Meranti) - Rizky Fitriyanti; Nur Azlina; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aim of this research is to analyzeThe Effect of Organization Commitment, Information Tehnology Utilization and Intern conrol system toward the performance of SKPD Government finance. (Empiric Study of SKPD Kabupaten Kepulauan Meranti).Sample of this research are 29 SKPD that located in meranti, Sampling technique is Purposive Sampling, the technique for testing Hypothesis using multiple analysis approach. The Result of this research shows that Organization commitment is affected to calculate value > table .3.266>2.030, Information Technology utilization significantly affect the calculate value > ttabel 2.383 >2.030 and intern control systemis significantly affect the calculate value > ttabel 2.419 > 2.030 toward Government’s finance performance.Keywords :Commitment, technology, Control, and performance.